Myocardial Fibrosis in Long-Distance Runners: From Physiological Adaptation to Potential Pathology - Prevalence, Imaging Characteristics, and Clinical Relevance - Kolasa, Magdalena; Kasterka, Natalia; Karbownik, Liwia; Figwer, Agnieszka; Figwer, Krzysztof; Dzitkowska, Kinga; Czarny, Norbert; Broniecka, Anna; Śmigielski, Michał; Garbaciak, Jędrzej (Quality in Sport, 2026)
In recent years, the popularity of long-distance running has increased considerably. Regular physical activity is widely recognized as an effective strategy for improving cardiorespiratory fitness, reducing the risk of cardiovascular disease, diabetes, obesity, multiple cancers, and ultimately contributing to increased life expectancy. Despite these well-established benefits, accumulated evidence suggests that prolonged exposure to high-volume endurance exercise may be associated with adverse structural cardiac remodeling in endurance athletes. Studies employing mainly cardiac magnetic resonance imaging (CMR) have identified myocardial abnormalities that may exceed the spectrum of physiological adaptation. Available data indicate the presence of myocardial fibrosis in some endurance athletes. Further research is needed to determine the clinical implications of these findings; however, several studies indicate that such changes may serve as a substrate for cardiac arrhythmias and, consequently, increase the risk of a sudden cardiac death. The aim of this review is to summarize current evidence regarding structural myocardial changes in long-distance runners, with particular emphasis on the prevalence, mechanisms, diagnostic assessment, and potential clinical consequences of myocardial fibrosis. Materials and Methods. A literature review was conducted using studies available in the PubMed and Google Scholar databases. The analysis included primarily original research articles, meta-analyses, and review papers focusing on myocardial fibrosis in endurance athletes.